‘It is a lifeline’: International cross-sectional survey of benefits, barriers and acceptability of online yoga during the COVID-19 pandemic - Tina Cartwright; Lindsay Metcalf; Vipin Wadhen (PLoS ONE, 2026)
Objectives Yoga is associated with physical and mental health benefits. Online delivery may increase access to these benefits, yet limited research has examined its effectiveness and acceptability. This cross-sectional study explored the perceived benefits, barriers, and acceptability of online yoga among a large, global sample of practitioners and teachers during the early phase of the COVID-19 pandemic. A secondary aim was to assess the psychosocial health of practitioners. Methods A total of 1,185 participants (511 yoga students, 586 yoga teachers) completed an online survey assessing sociodemographic characteristics, yoga dosage, perceived benefits and barriers, and psychosocial health indicators (social isolation, depression, anxiety, and stress). Open-ended responses were analyzed using inductive thematic analysis to identify perceived challenges and benefits of online yoga. Results Participants reported low levels of stress, anxiety, and depressive symptoms compared to general population norms during the pandemic. Hierarchical regressions showed small but significant associations between yoga practice and mental health. Controlling for age and gender, days per week was associated with lower depression (β = −.10, p = .011) and years of practice with lower anxiety (β = −.07, p = .045). Age was inversely associated with depression, anxiety, and stress. Both quantitative and qualitative data indicated that the benefits of online yoga outweighed its barriers. Key reported benefits included social connectedness, increased accessibility and convenience, improved mental and physical health, and opportunities for personal practice. Reported barriers included reduced group connection, limited personalized guidance, and practical challenges related to technology and the home environment. Conclusions This mixed-methods study offers novel insights into the perceived effectiveness and limitations of online yoga from both student and teacher perspectives. Interpreted through the COM-B model, findings highlight key barriers and facilitators that can inform the future design and delivery of online and hybrid yoga interventions in a post-pandemic context.